From 'rational' to 'Sufi Islam'?: The changing place of Muslims in Tamil nationalism - Tschacher, Torsten (Islam, Sufism and everyday politics of belonging in South Asia, 2016)
While studying for my MA, I spent a year at the Department of Anthropology at Pondicherry University. Among other tasks, my local guide had given me the assignment to study a particular Muslim shrine in a predominantly Muslim town some 50 kilometers south of Pondicherry. Before leaving India, I had to visit the registration office to inform local officials that my exchange had come to an end and I would be returning to my home country soon. I was treated to tea and some snacks as I was politely questioned about the activities I had engaged in during my exchange by the same official who had registered my arrival 12 months earlier. I mentioned the assignment at the dargāh, and was innocuously asked what I had learned from this assignment. Seeing where this was going, I told of the astonishing harmony between Hindus, Muslims and Christians visiting the shrine and the shared culture of worship I supposedly encountered. The face of the official registered friendly satisfaction with my answer, a satisfaction that I believe derived as much from my glorification of Indian ‘unity in diversity’ as from the fact that I had understood what the politically correct answer had been that I was supposed to give.